Study the Genetic Variance of Genotypes of Maize (Zea mays L.): ????? ??????? ??????? ??????? ?????? ?? ????? ??????? ( .Zea mays L) (NTU Journal of Agriculture and Veterinary Science, 2024)
The experiment was conducted in the fields of the College of Agriculture and Forestry University of Mosul for the autumn season 2022-2023, and Ten genotypes were used, namely (DR-F-53, MA-F-53, H-4, DKC-F-59, IK-58, ZP-595, POL-F-6, SYM-F-53, MY-F-53 and SYN-F-54) To study the genetic stability of genotypes of maize according and the experiment was a The Randomized Complete Block Design (R.C.B.D) was used with three replicates and the traits of studied (date of tasseling , date of silking , number of ears per plant , number of grains per ear , weight of 500 grains, single plant production) . The results showed that in terms of genetic, phenotypic and environmental variations, heritability in the broad sense, and the expected genetic improvement as a percentage, it was high for all genotypes and for all traits, and this gives an opportunity for selection for these superior traits.